De Jacó a Moisés: conexões literárias entre o Gênesis e o Êxodo: um olhar a partir da narrativa de José e de Ex 1,1-14 - SANTOS, Jheymes França Correia dos. (2023)
The stories of Israel’s ancestors are largely cycles of separate stories, each having its own tradition, coming from a different place and time. These traditions were later brought together by a ‘final redactor’ who would have left the marks of his work in evidence. This research analyzes the literary connections that would have united the tradition of the patriarchs with the Exodus tradition, set out in the Joseph narrative, in the passage from Gen 37-50 and in the opening of the book of Exodus, in the passage from Ex 1,1-14. The research offers some essays on how the traditions of Genesis and Exodus would have been joined together as part of a continuous literary unit. The narrative of Joseph and his brothers would have emerged during the Persian period as a “diaspora novella” and only later would have been stitched into Genesis to bridge the traditions of Israel’s patriarchs and the events of the Exodus. Several parts of Exodus 1,1-14 would be literary constructions built on the issues developed in Genesis and would be coherent only when read in continuity with Genesis. The connection between the traditions of the patriarchs and the exodus could be considered a feature of the early formation of the Pentateuch, similar to its final construction.(AU)